(untitled) (Indian Journal of Animal Production and Management, 2024)
Pig production occupies an important place in modern agriculture. Piglets are far less demanding on nutrients as compared to poultry. The experiment was conducted to know the effect of feeding organic and inorganic sources of additional zinc on growth incidences of gut microbial status in piglets. Sixty graded (Large White Yorkshire) suckling piglets were randomly divided into three treatment groups of twenty piglets each based on litter size, parity and live birth weight. Treatment I (T1) served as control and these piglets were fed with deionized water daily as oral suspension. Treatment II (T2) and Treatment III (T3) were fed with fed Zinc Oxide (ZnO) and Zinc Methionine (ZnM) daily (50 ppm) as oral suspension. The results of the experiment showed that the incidence of mortality in control (T1), zinc oxide (T2) and zinc methionine (T3) groups were 10, 5 and 0 per cent, respectively. Statistical analysis revealed that there was no significant difference between control (T1), zinc oxide (T2) and zinc methionine (T3) groups. Based on the results of the current experiment and the reports available, the importance of supplementation of zinc oxide at higher than the recommended dosage may be considered for maintaining the proper growth, health and production status of piglets.